Brazilian real-world data of immunotherapy in extensive stage small cell lung cancer - Duarte, Flavia A.; Dienstmann, Rodrigo; Diniz, Paulo H. C.; e Silva, Matheus C.; Veloso, Gilson G. V.; Arcanjo, Georgia S.; Paes, Rafael; Montella, Tatiane C.; Lima, Helena F. C. A.; Ferrari, Bruno L.; Macuzo, Eliane V.; Ferreira, Carlos G. (Frontiers in Oncology, 2025)
IntroductionThe landmarks of Thoracic Oncology in the last two decades have been accompanied by exponential growth in costs, making it imperative to assess the real benefit of incorporating new technologies. Combining immunotherapy (IO) with platinum-etoposide chemotherapy has become the standard of care in first-line treatment of extensive-stage small cell lung cancer (ES-SCLC). However, the absolute difference in overall survival (OS) has reached three months. This study aimed to investigate the impact of this intervention in a real-world cohort.Material and methodsWe retrospectively analyzed data from ES-SCLC patients (pts) from a Brazilian Oncology Group, diagnosed and treated between January 2018 and June 2022. The primary objectives were median OS (mOS) and median time to subsequent treatment (mTST) according to IO exposure in the first-line setting. Secondarily, we intend to compare these results with the literature data and with an internal and contemporary cohort of patients treated with chemotherapy alone.ResultsIn total, 85 SCLC patients were included in this analysis. The median follow-up was nine months. First line regimens were atezolizumab + platinum-etoposide in 53%, platinum-etoposide in 36% and platinum-irinotecan in 11%. Among ES-SCLC pts who received IO in their first-line treatment, the mOS was 15.0 months (95% CI: 11.20; 18.80) and the mTST was 8.0 months (95% CI: 6.25; 9.75). As a reference, our internal and contemporary control presented numerically lower mOS and mTST: 9.0 months (95% CI: 2.08; 19.92) and 7.0 months (95% CI: 5.88; 8.12), respectively.DiscussionFew real-world cohorts are evaluating the impact of IO in ES-SCLC, limited to high-income countries. Our data suggest that IO has a meaningful impact on the outcome of ES-SCLC in daily clinical practice, confirming previous trial results.